Intravenous cangrelor use for neuroendovascular procedures: a two-center experience and updated systematic review - Desai, Harsh; Al-Salihi, Mohammed Maan; Morsi, Rami Z.; Vayani, Omar R.; Kothari, Sachin A.; Thind, Sonam; Carrión-Penagos, Julián; Baskaran, Archit; Tarabichi, Ammar; Bonderski, Veronica A.; Siegler, James E.; Hahn, Mary; et al. (Frontiers in Neurology, 2023)
The optimal antiplatelet therapy regimen for certain neuroendovascular procedures remains unclear. This study investigates the safety and feasibility of intravenous dose-adjusted cangrelor in patients undergoing acute neuroendovascular interventions.We conducted a retrospective chart review of all consecutive patients on intravenous cangrelor for neuroendovascular procedures between September 1, 2020, and March 13, 2022.We also conducted an updated systematic review and meta-analysis using PubMed, Scopus, Web of Science, Embase and the Cochrane Library up to February 22, 2023.Results: In our cohort, a total of 76 patients were included [mean age (years): 57.2 ± 18.2, males: 39 (51.3), Black: 49 (64.5)]. Cangrelor was most used for embolization and intracranial stent placement (n=24, 32%). Approximately 44% of our patients had a favorable outcome with a modified Rankin Scale (mRS) score of 0 to 2 at 90 days (n=25/57); within 1 year, 8% of patients had recurrent or new strokes (n=5/59), 6% had symptomatic intracranial hemorrhage[sICH] (4/64), 3% had major extracranial bleeding events (2/64), and 3% had a gastrointestinal bleed (2/64). In our meta-analysis, 11 studies with 298 patients were included. The pooled proportion of sICH and intraprocedural thromboembolic complication events were 0.07 [95% CI 0.04 to 1.13] and 0.08 [95% CI 0.05 to 0.15], respectively.Conclusions: Our study found that intravenous cangrelor appears to be safe and effective in neuroendovascular procedures, with low rates of bleeding and ischemic events. However, further Desai 4 research is needed to compare different dosing and titration protocols of cangrelor and other intravenous agents.